Scooby-Doo! and the monster of Mexico - Dean, Margaret M.; Jeralds, Scott; Wood, Douglas; Kasem, Casey; Welker, Frank; Jaffe, Nicole; North Kenny, Heather, 1950-; Borrego, Jesse, 1962-; Canals, Maria, 1966-; Gonzales, Brandon; Moreno, Rita.; Yang, Bunis; et al. (Burbank, CA : Warner Home Video, 2003)
Fred, Daphne, Velma, Shaggy, and Scooby-Doo go to Mexico to visit Fred's computer pen pal and to celebrate the Day of the Dead festivities, which become less festive when a towering, glowering Chupacabra monster turns up to terrify both tourists and locals. The young snoops smell a conspiracy, and as they chase down clues their search for the truth leads them into sundry Mexican antiquities - ancient tombs and temples - where danger increases exponentially.
Based on the characters created by Hanna-Barbera Productions.
Special features: "Watch the movie with the gang" commentary by Scooby-Doo, Shaggy and Fred; the making of 'Monster of Mexico'; behind-the-scenes 'Monster of Mexico' scrapbook; bloopers/outtakes; trailers.
Animation director, Bunis Yang ; editor, Joe Gall ; music, Gigi Meroni, Rich Dickerson ; character designers, Scott Awley, Scott Jeralds.
Voices: Casey Kasem, Frank Welker, Nicole Jaffe, Heather North Kenny, Jesse Borrego, Maria Canals, Brandon Gonzales, Rita Moreno.
DVD, Region 1 encoding, Dolby digital.
Closed-captioned.
Keywords: Scooby-Doo (Fictitious character) -- Juvenile drama; Private investigators -- Juvenile drama; All Souls' Day -- Juvenile drama; Animated television programs -- United States; Television programs for children -- United States; Video recordings for the hearing impaired